Everyday Functioning in Huntington's Disease: A Laboratory-Based Study of Financial Management Capacity. Issue 2 (4th March 2017) - Sheppard, David P.; Pirogovsky-Turk, Eva; Woods, Steven Paul; Holden, Heather M.; Nicoll, Diane R.; Filoteo, J. Vincent; Corey-Bloom, Jody; Gilbert, Paul E.
ABSTRACT: One important limitation of prior studies examining functional decline in Huntington's disease (HD) has been the reliance on self-reported measures of ability. Since report-based methods can be biased by lack of insight, depression, and cognitive impairment, contrasting self-reported ability with measures that assess capacity may lead to a more comprehensive estimation of real-world functioning. The present study examined self-reported ability to perform instrumental activities of daily living (iADLs) and performance-based financial management capacity in 20 patients diagnosed with mild-moderate Huntington's disease (HD) and 20 demographically similar healthy adults. HD patients reported significantly greater declines in their ability to manage finances. On the capacity measure of financial management, HD patients performed significantly below healthy adults. Additionally, in the HD group there were no significant correlations between self-reported ability and capacity measures of financial management. HD patients endorsed declines in global iADL ability and exhibited deficits in functional capacity when performing a financial management task. Capacity measures may aid in assessing the extent to which HD patients accurately estimate real-world iADL performance, and the present findings suggest that such measures of capacity may be related to the cognitive, but not motor or affective, symptoms of HD.